P464 Treatment failure in rectal Chlamydia trachomatis azithromycin treated women driven by high viable bacterial load (FemCure). (14th July 2019) - Dukers-Muijrers, Nicole; Wolffs, Petra; Vries, Henry De; Götz, Hannelore; Heijman, Titia; Janssen, Kevin; Bruisten, Sylvia; Hogewoning, Arjan; Steenbakkers, Mieke; Lucchesi, Mayk; Loeff, Maarten Schim Van Der; Hoebe, Christian
Abstract : Background: Rectal infections with Chlamydia trachomatis (CT) are prevalent in women visiting a STI outpatient clinic. While azithromycin is the most used treatment, microbiological treatment failure in rectal CT is common and its drivers remain unclear. Methods: This study is part of a prospective multicentre cohort study (FemCure). Current analyses included 112 women clinically-diagnosed (by nucleic acid amplification test [NAAT]) with rectal and vaginal CT, who not vomited and denied rectal and vaginal unprotected sex. Four weeks after azithromycin treatment (1g single dose) participants self-collected vaginal and rectal samples. Samples were tested for CT-DNA (NAAT) and viable CT-load (viability polymerase chain reaction [V-PCR]). We evaluated two endpoints: (1) failure by NAAT-positivity and (2) failure by V-PCR-positivity. Enrolment-risk-factors associated with failure were assessed using multivariable logistic regression; i.e., age, education, migratory-background, previous CT, NAAT Cq-value [marker CT-DNA load], culture, viable CT [V-PCR positive], viable load [log10 copies/ml], vaginal CT. Results: (1) Failure by NAAT (21.4%; 24/112) was independently associated with both rectal and vaginal NAAT Cq-values; both aOR: 0.8 per unit decrease in the NAAT Cq-value (95%CI:0.7–0.9, p<0.01). Of the 49 women with a rectal or vaginal Cq-value ≥36 at clinic-diagnosis (43.8% of patients), 8.1% had rectal failure, compared to 31.7% when having Cq values <=36 (p<0.01). (2) Failure by V-PCR (16.1%;18/112) was independently associated with the rectal viable load; aOR: 1.7 per log10 copies/ml increase (95%CI:1.3–2.3). Of the 47 (42.0%) women without a viable rectal CT at diagnosis, 4.3% had failure, compared to 24.6% when having viable rectal CT at diagnosis (p<0.01). Vaginal failure by NAAT was 7.1% (8/112); failure by V-PCR was 2.7% (3/112). Conclusion: In an outpatient clinical setting, azithromycin rectal CT microbiological treatment failure was common and associated with higher pre-treatment (viable) loads. The lower azithromycin treatment failure in patients with NAAT Cq-values≥36 or non-viable rectal CT might result in different treatment choices. Disclosure: No significant relationships.